鼓式制动器凸轮型线对其制动性能影响的研究 - 张安静; 徐延海; 吕欣 (Jixie chuandong)
Based on the analysis of the factors which affect the braking force of a heavy vehicle drum brake driven by cam,the applied force at leading and trailing hoof and cam profile are systematically investigated.The relationship of the center distance between cam and roller and the force arm of the applied forces is studied as well as the relationship of cam rotation angle and the applied force.Finally,the influence of cam profile on the applied force at braking hoof is analyzed under three typical stages of worn shoes,the quantitative relationship between cam profile and applied force is given as well.It is shown from the study that the optimization of cam profile can great improve braking efficiency and vehicle safety.